Psychometric properties of the «Spanish Burnout Inventory» (SBI) in a sample of Italian health professionals: a gender perspective - Gil-Monte, Pedro (2017)
The purpose of this study was to assess the psychometric properties of the Spanish Burnout Inventory (SBI) in a sample of Italian health professionals. The sample consisted of 695 participants: 453 nursing professionals and 242 physicians. Regarding the gender, 451 were women (64.9%) and 244 were men (35.1%). The SBI is composed of 20 items distributed in four dimensions: Enthusiasm towards the job (5 items), Psychological exhaustion (4 items), Indolence (6 items) and Guilt (5 items). The factor structure was examined through confirmatory factor analysis. All items achieved appropriate values for both statistical and psychometric parameters, just as the four scales did. The four-factor model consistent with the Spanish original obtained a good data fit for the whole sample, showing factor invariance in both samples (i.e., men vs. women). In conclusion, the SBI has adequate psychometric properties to study the burnout syndrome in Italian health professionals, regardless of their gender.